Editorial: Dissonance Between Formal Policy and Social Reality in Contemporary Governance - Dias Pabyantara Swandita Mahayasa; Arum Tri Utami (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2026)
Editorial: Dissonance Between Formal Policy and Social Reality in Contemporary Governance